Mapping Fifth-Grade Students Conceptual Understanding of Cube Powers and Cube Roots: A Descriptive Study at SD Negeri 2 Kendari - Ilham, Muhammad; Agus, Imaludin; Hasnia, Hasnia; Rohman, Asep Saeful (Jurnal Didaktika Pendidikan Dasar, 2025)
This study aims to map the conceptual understanding of fifth-grade students at SD Negeri 2 Kendari regarding cube powers and cube roots. Using a qualitative descriptive approach, the research investigates three indicators of conceptual understanding: classification of mathematical objects, selection and use of procedures, and application of concepts in problem-solving. Data were collected through a written conceptual-understanding test and follow-up interviews with students representing high-, medium-, and low-performance groups. The findings show that students’ conceptual understanding is uneven across indicators. Most students demonstrated adequate ability to classify cubic numbers and identify structural characteristics of cube powers. However, substantial difficulties emerged in selecting appropriate procedures and understanding the multiplicative structure underlying cube powers and their inverse operations. Misconceptions, such as interpreting cubing as repeated addition or treating cube roots as simple division—were evident among medium- and especially low-performing students. Problem-solving posed the greatest challenge, with many students struggling to integrate information, select relevant operations, or apply concepts in contextual situations. Overall, the study provides a detailed profile of students’ conceptual strengths and challenges, offering insights that can inform instructional improvement. The results highlight the need for learning experiences that emphasize conceptual relationships, multiple representations, and explicit correction of misconceptions to support deeper mathematical understanding.